(untitled) (African Scientific Reports, 2025)
This article has been retracted by the Editor-in-Chief of African Scientific Reports following post-publication concerns regarding the accuracy and appropriateness of several cited references and their correspondence to the statements for which they were cited, particularly in relation to methodological and disease-specific claims. In line with standard editorial practice, the authors were invited to review these issues and to submit a corrected version of the manuscript to ensure that all citations accurately and appropriately supported the text. Unfortunately, the requested corrections could not be completed. To ensure the accuracy and reliability of the scholarly record, and in accordance with the journal’s editorial policies and the Committee on Publication Ethics (COPE) guidelines, the Editor-in-Chief, on behalf of the Editorial Board, has therefore decided to retract this article. This action is taken solely to maintain the integrity of the published record. No determination has been made regarding the intent of the authors. The article will remain accessible for reference purposes but will be clearly marked as retracted. A separate retraction notice is available at: https://doi.org/10.46481/asr.2026.5.1.451